Global Youth Engagement in Promoting Community Empowerment in Indonesian Geoparks Development: Prospects and Challenges for Indonesia Geopark Youth Forum - Diemas Sukma Hawkins (Journal of Social Development Studies, 2022)
Geoparks are a fairly new concept, raising to popularity only around the very end of the twentieth century with the formation of the United Nations Educational, Scientific and Cultural Organization Global Geoparks Network (UNESCO GGN). Indonesia currently has six geoparks designated as UNESCO Global Geoparks, as well as fifteen national geoparks and several aspiring geoparks. The National Committee for Indonesain Geoparks which is headed by three coordinating ministries and three technical ministries with twelve other ministries and agencies as members of the committee has identified that youths hold a critical role in the development of geoparks in Indonesia. This was stated clearly in the National Action Plan for Indonesian Geoparks in Ministry of National Development Planning No. 15/2020. In 2021 the Ministry for National Development Planning sought out to realize this by forming the Indonesian Geopark Youth Forum, a youth-led organisation where representatives of Indonesian geoparks help actualize the development of Indonesian geoparks and their local communities. As IGYF continues to develop in its infancy with the hosting of the 1st UNESCO Geopark Youth Forum in Jeju Island, South Korea resulting in the election of Indonesia as the host country and chairman for the UNESCO Geopark Youth Forum for 2021-2023, the author in this paper attempts to give an analysis of the role that IGYF has as a new actor catalyst in the sustainable development of communities in the geopark areas through the unique approach that geoparks have, with great focus on community empowerment as the foundation for the development of the three pillars of geoparks; education, conservation, and sustainable economic development.